MYCN amplification drives an aggressive form of spinal ependymoma - Ghasemi, David R.; Sill, Martin; Korshunov, Andrey; Maaß, Kendra K.; Witt, Hendrik; Kawauchi, Daisuke; Herold-Mende, Christel; Sahm, Felix; Kool, Marcel; Jones, David T. W.; Deimling, Andreas von; Pfister, Stefan; et al. (Acta neuropathologica, 2019)
Spinal ependymal tumors form a histologically and molecularly heterogeneous group of tumors with generally good prognosis. However, their treatment can be challenging if infiltration of the spinal cord or dissemination throughout the central nervous system (CNS) occurs and, in these cases, clinical outcome remains poor. Here, we describe a new and relatively rare subgroup of spinal ependymal tumors identified using DNA methylation profiling that is distinct from other molecular subgroups of ependymoma. Copy number variation plots derived from DNA methylation arrays showed MYCN amplification as a characteristic genetic alteration in all cases of our cohort (n = 13), which was subsequently validated using fluorescence in situ hybridization. The histological diagnosis was anaplastic ependymoma (WHO Grade III) in ten cases and classic ependymoma (WHO Grade II) in three cases. Histological re-evaluation in five primary tumors and seven relapses showed characteristic histological features of ependymoma, namely pseudorosettes, GFAP- and EMA positivity. Electron microscopy revealed cilia, complex intercellular junctions and intermediate filaments in a representative sample. Taking these findings into account, we suggest to designate this molecular subgroup spinal ependymoma with MYCN amplification, SP-EPN-MYCN. SP-EPN-MYCN tumors showed distinct growth patterns with intradural, extramedullary localization mostly within the thoracic and cervical spine, diffuse leptomeningeal spread throughout the whole CNS and infiltrative invasion of the spinal cord. Dissemination was observed in 100% of cases. Despite high-intensity treatment, SP-EPN-MYCN showed significantly worse median progression free survival (PFS) (17 months) and median overall survival (OS) (87 months) than all other previously described molecular spinal ependymoma subgroups. OS and PFS were similar to supratentorial ependymoma with RELA-fusion (ST-EPN-RELA) and posterior fossa ependymoma A (PF-EPN-A), further highlighting the aggressiveness of this distinct new subgroup. We, therefore, propose to establish SP-EPN-MYCN as a new molecular subgroup in ependymoma and advocate for testing newly diagnosed spinal ependymal tumors for MYCN amplification.
Gesehen am 05.05.2020